Single-cell Whole RNA Sequencing from Tumor-Infiltrating Lymphocyte - Biaoru Li; Yunbo Xu (New Horizons in Medicine and Medical Research Vol. 10, 2022)
The study highlights a genomic approach combining single-cell mRNA differential display and RNA subtractive hybridization to elucidate the CD8 T-cell silence ten years ago. To study the feasibility of the whole RNA sequencing technique (RNA-seq) for gene expression at a single-cell level, here, we used one similar RNA specimen from the amplified RNA to run RNA high-throughput transcriptome sequencing (RNA-Seq). We found that results of RNA-seq were higher related to those of single-cell mRNA differential display and single-cell qPCR. The pair correlation of gene expression levels from normalized RPKM (reads per kilobase of transcript per million mapped reads) was 0.58-0.81 to those from qrtPCR among genes, which were uncovered for up-regulated genes (Tob, TGF- \(β\) , LKLF, SnoA, Ski, Myc, ERF and REST/NRSF complex) in the T-cell silent status. The results demonstrate the feasibility of using RNA-Seq to study the transcriptome at the single-cell level.